KEPASTIAN HUKUM PEMIDANAAN TERHADAP DELIK KETERANGAN TIDAK BENAR ATAU MENGGUNAKAN SURAT PALSU SEBAGAI CALON BUPATI PILKADA (STUDI KASUS DI SABU RAIJUA PUTUSAN MK NOMOR : 135/PHP.BUP-XIX/2021) - Mazmur Prima Dimu Heo; Rugun Romaida Hutabarat (Jurnal Hukum Adigama, 2021)
Indonesia applies as a single citizenship (monopartite) for those who are legally capable or are 18 years old based on Law Number 12 of 2006 concerning citizenship, but what attracts attention is the dual citizenship of the candidate for Regent in Sabu Raijua Orient Patriot Riwu Kore who has American passport which means automatically being a citizen of the United States (US) and at the same time Oriet Patriot Riwu Kore masi is registered as an Indonesian citizen (WNI), based on the conditions that must be met to become a candidate for regional head as stipulated in the Act. Law number 10 of 2016 concerning Regional Head Elections (Pilkada) which states that only Indonesian citizens can become candidates for Regional Head, because of that formally fully the requirements to be appointed as a candidate for Regent contains formal legal defects because only Indonesian citizens should (WNI) only can calo n himself as a candidate for regent. Therefore, the determination of the Orient Patriot Riwu Kore as regent of the candidate pair 2 must prove that it is against the law (illegal) or null and void (null and void or void ab initio). Further, based on the decision of the Constitutional Court Number: 135/PHP.BUP-XIX/2021 only administrative sanctions were given, namely the disqualification of candidate pair number 2, Orient Patriot Riwu Kore and a re-vote (PSU) criminal sanctions for being dishonest or providing incorrect information regarding their citizenship status.